The basic features of Einstein equations with cosmological term, which linearly dependents from the space-time Riemann curvature scalar - Vil'chinsky, S. I.; Nakaznoy, P. A. (Одеські астрономічні публікації, 2017)
The model of variable cosmological term, which linearly dependents from the space- time Riemann curvature scalar is proposed. The basic features of such model: Friedmann equations, their solutions, its asymptotic forms, energy integrals for each kind of matter, newton limit is considered. Especially we have tried to describe observation data of galaxies rotation curves without recourse of dark matter. The positive and negative aspects of this method of attack is reviewed.